Implications of Probiotics on the Maternal-Neonatal Interface: Gut Microbiota, Immunomodulation, and Autoimmunity - Swartwout, Brianna; Luo, Xin M. (Frontiers in Immunology, 2018)
Probiotics are being investigated for the treatment of autoimmune disease by re-balancing dysbiosis induced changes in the immune system. Pregnancy is a health concern surrounding autoimmune disease, both for the mother and her child. Probiotics for maternity are emerging on the market and have gained significant momentum in the literature. Thus far, evidence supports that probiotics alter the structure of the normal microbiota and the microbiota changes significantly during pregnancy. The interaction between probiotics-induced changes and normal changes during pregnancy is poorly understood. Furthermore, there is emerging evidence that the maternal gut microbiota influences the microbiota of offspring, leading to questions on how maternal probiotics may influence the health of neonates. Underpinning the development and balance of the immune system, the microbiota, especially that of the gut, is significantly important, and dysbiosis is an agent of immune dysregulation and autoimmunity. However, few studies exist on the implications of maternal probiotics for the outcome of pregnancy in autoimmune disease. Is it helpful or harmful for mother with autoimmune disease to take probiotics, and would this be protective or pathogenic for her child? Controversy surrounds whether probiotics administered maternally or during infancy are healthful for allergic disease, and their use for autoimmunity is relatively unexplored. This review aims to discuss the use of maternal probiotics in health and autoimmune disease and to investigate their immunomodulatory properties.